(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2011)
Corruption, in all its categories and forms, is regarded as the nowadays virus which has greatly spread in most institutes and society, a matter that cause a great waste of resources. According to the reports of international transparency Institute, Iraq is regarded as one of the greatest countries in corruption. Regardless of the reasons and forms of corruption, the retreat in work – values and ethics are the main reasons behind that. Being the main source of providing qualified staff "educators" for the working market, the high education institutes face great challenges in standing against corruption inside and outside them. They can face it through various aspects such as re-evaluating and re-building curricula and supporting them with job-ethics and programs for fighting against corruption, Preparing qualified teachers, The internal systems of education institute and strengthening the latter’s role in serving the society as far as fighting against corruption is concerned.